Early treatment using fractional CO2 laser before skin suture during scar revision surgery in Asians. (17th February 2018) - Du, Feiya; Yu, Yusheng; Zhou, Zhiqin; Wang, Liujia; Zheng, Shusen
ABSTRACT: Fractional CO2 laser is one of the most effective treatment options used to resurface scars. However, most previous studies have been performed on mature scars at least 2 months after surgery. Recent studies have emphasized the importance of early treatment to reduce scar formation. In the present study, we described our experience with fractional CO2 laser intervention before skin suture during scar revision surgery in Asians, and found the treatment was safe and effective.